Mercury Exposure among Garbage Workers in Southern Thailand - Somsiri Decharat (Elsevier, 2012)
Objectives: 1) To determine mercury levels in urine samples from garbage workers in Southern Thailand, and 2) to describe the association between work characteristics, work positions, behavioral factors, and acute symptoms; and levels of mercury in urine samples. Methods: A case-control study was conducted by interviewing 60 workers in 5 hazardous-waste-management factories, and 60 matched non-exposed persons living in the same area of Southern Thailand. Urine samples were collected to determine mercury levels by cold-vapor atomic absorption spectrometer mercury analyzer. Results: The hazardous-waste workers' urinary mercury levels (10.07 μg/g creatinine) were significantly higher than the control group (1.33 μg/g creatinine) (p < 0.001). Work position, duration of work, personal protective equipment (PPE), and personal hygiene, were significantly associated with urinary mercury level (p < 0.001). The workers developed acute symptoms - of headaches, nausea, chest tightness, fatigue, and loss of consciousness at least once a week - and those who developed symptoms had significantly higher urinary mercury levels than those who did not, at p < 0.05. A multiple regression model was constructed. Significant predictors of urinary mercury levels included hours worked per day, days worked per week, duration of work (years), work position, use of PPE (mask, trousers, and gloves), and personal hygiene behavior (ate snacks or drank water at work, washed hands before lunch, and washed hands after work). Conclusion: Changing garbage workers' hygiene habits can reduce urinary mercury levels. Personal hygiene is important, and should be stressed in education programs. Employers should institute engineering controls to reduce urinary mercury levels among garbage workers.